2015
DOI: 10.5492/wjccm.v4.i1.89
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic epidural anesthesia: Effects on splanchnic circulation and implications in Anesthesia and Intensive care

Abstract: AIM:To evaluate the currently available evidence on thoracic epidural anesthesia effects on splanchnic macro and microcirculation, in physiologic and pathologic conditions. METHODS:A PubMed search was conducted using the MeSH database. Anesthesia, Epidural was always the first MeSH heading and was combined by boolean operator AND with the following headings: Circulation, Splanchnic; Intestines; Pancreas and Pancreatitis; Liver Function Tests. EMBASE, Cochrane library, ClinicalTrials. gov and clinicaltrialsregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
(102 reference statements)
0
16
0
Order By: Relevance
“…Richards et al [ 6 ] published in 2013 a systemic review which could not establish the real impact of TEA on splanchnic perfusion. Siniscalchi et al [ 7 ] also stated that studies focusing on regional macrocirculation could not show an influence on, or even showed worsening of, regional perfusion when TEA was used. In contrast, studies focusing on microcirculation, especially in pathologic flow conditions such as the state induced by AP, suggested that TEA could improve microcirculation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Richards et al [ 6 ] published in 2013 a systemic review which could not establish the real impact of TEA on splanchnic perfusion. Siniscalchi et al [ 7 ] also stated that studies focusing on regional macrocirculation could not show an influence on, or even showed worsening of, regional perfusion when TEA was used. In contrast, studies focusing on microcirculation, especially in pathologic flow conditions such as the state induced by AP, suggested that TEA could improve microcirculation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Siniscalchi et al [ 7 ] also stated that studies focusing on regional macrocirculation could not show an influence on, or even showed worsening of, regional perfusion when TEA was used. In contrast, studies focusing on microcirculation, especially in pathologic flow conditions such as the state induced by AP, suggested that TEA could improve microcirculation [ 7 ]. There is growing evidence that microcirculation plays a crucial role in AP, and no treatment except TEA has proven to play a role in this aspect.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this prospective single cohort study, epidural analgesia was thus able to produce considerable analgesic effect without any major rate of complications (10). Therefore, based on these promising observations, the results of the three clinical trials that are currently investigating the effect epidural analgesia on the course of AP are eagerly awaited (70).…”
Section: Novel Strategies Of Pain Management In Apmentioning
confidence: 99%